Development of a Mobile Application Using Augmentative and Alternative Communication and Video Modelling for Autistic Children - Zulkharnain, Nur Adilla (IRC, 2020)
A mobile application which uses the video modelling and Augmentative and Alternative Communication approach is developed on a device such as tablet and mobile phone. Video modelling is an approach that has been used as a teaching method where an individual watched a video of someone performing an action such as brushing teeth and imitate that action, meanwhile, AAC is a form of a communication that helps people who struggle to communicate properly like a normal person. As the number of autistic children increasing each year, the quality of teaching aid needs to be improved to enhance their skills. However, there are lack of current mobile app that can help ASD children carrying out their daily life routine and enhance their character building to shape them to be a better person. Therefore, this project aims to identify how to integrate AAC and video modelling approach, to develop the mobile application and to conduct the usability testing. Requirement gathering is done through literature review of research papers, observation, questionnaire and interview. At the same time, this project methodology is based on Rapid Application Development (RAD), which has an outcome of a project’s prototype which is a mobile application that called AutiAct. Later, the testing has been conducted where an observation has been conducted with 4 ASD children that aged from 7 to 12 years old where each of them has different type of severity meanwhile usability testing and interview questions has been conducted with 3 teachers from The National Autism Society of Malaysia (NASOM) to test the effectiveness of AutiAct. In summary, AutiAct is reliable to help autistic children to enhance their independent skills so they will less depend on their parents as they are getting older and it also embed some character building for autistic children to help them shape their personality and characteristics.